Tinjauan Yuridis Pekerja Alih Daya (Outsourcing) Setelah Berlakunya Peraturan Pemerintah Nomor 35 Tahun 2021 - Muhammad Alfian Sangaji; Lalu Hadi Adha (Fakultas Hukum Universitas Mataram, 2023)
This study purposed to figure out the differences in the regulation of outsourced labor before and after the enactment of Government Regulation Number 35 of 2021. This study applying normative research method that uses positive law as a building norm system. Outsourcing is one type of work that oftenly used by companies to supporting their work load. In the regulations itslef, there are still gap that harm the rights of outsourced workers. Therefore, the government is trying to fix this gap by making a new regulation, namely Government Regulation Number 35 of 2021 Regarding Outsourcing, which is simpler and guarantees the rights of outsourced workers.